EDUCATION RESILIENCE IN THE FACE OF CRISIS: FACTORS CONTRIBUTING TO THE EFFECTS OF COVID-19 ON STUDENT PERFORMANCE - Shahzada Khayyam Nisar; Amna Nabeel; Sharifah Muzlia Syed Mustafa; Khadijah Said Hashim (Journal of Islamic, Social, Economics and Development, 2024)
The COVID-19 pandemic changed the global educational environment by shifting the focus from physical to online learning setups. These changes had both positive and negative impacts on student performance. However, some factors played a vital role in determining the influence of covid-19 pandemic on student performance. These factors were examined in this paper to identify the extent to which student performance has been influenced by the pandemic. The paper incorporated technological limitations, social disparity, mental health challenges, changes in pedagogical methods, and parental involvement and support as primary factors that determined the influence of the pandemic on student performance. After describing the influence of these factors, the research paper discussed mitigation strategies to minimize their negative influence on student’s performance, enable students, teachers, and educational institutes to maximize the benefits of online learning systems and prepare them to deal with future challenges related to learning and development objectives.